Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1038416219886116
|View full text |Cite
|
Sign up to set email alerts
|

Identifying best practice in career education and development in Australian secondary schools

Abstract: This review aimed to identify the tenets of best practice in career education and development within Australian schools. Analysis of 13 articles revealed that career education and development is increasingly recognised as the critical transitional mechanism for young people. An embedded, whole-school approach with services tailored to the individual, school, community and culture was a central theme. Furthermore, one-on-one counselling by appropriately resourced and qualified professionals, provision of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…The empirical contribution of this paper is the three main themes identified in the perspectives of regional communities to inform curriculum design and practices. The first theme, the need for simple, easy to teach career activities links to ongoing research that discussed how to balance what some scholars have described as a crowded curriculum (Keele et al, 2020 ). Wyn ( 2007 ), speaking on health and wellbeing, however, argues that non-core curriculum topics are marginalised not because of available time, but because of they are not valued within policy frameworks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical contribution of this paper is the three main themes identified in the perspectives of regional communities to inform curriculum design and practices. The first theme, the need for simple, easy to teach career activities links to ongoing research that discussed how to balance what some scholars have described as a crowded curriculum (Keele et al, 2020 ). Wyn ( 2007 ), speaking on health and wellbeing, however, argues that non-core curriculum topics are marginalised not because of available time, but because of they are not valued within policy frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, teachers have been identified as best placed to deliver careers activities (Welde et al, 2015 ), supporting the long-standing view of embedding careers education in the curriculum. Given the marked socioeconomic divide in the type and quality of career information available to students (Dockery et al, 2021 ) researchers have advocated for a whole school approach to “embed career education and development in curriculum/co-curriculum, beginning with exploratory activities in primary school and linking these to further exploration, reflection and adaptive goal setting in later years” (Keele et al, 2020 , p. 57) and developing a “curriculum that explicitly teaches students the ‘hidden’ discourses to navigate the world of work” (Austin et al, 2021 , p. 6).…”
Section: Career Education In the Australian Curriculummentioning
confidence: 99%
“…To transition from one phase to another, young athletes have to meet challenging demands that may be stressful and require commitment. This implies that wide and open approaches toward career development for student athletes are required to systematically prepare and design their future careers [20].…”
Section: Career Development For Adolescentsmentioning
confidence: 99%
“…Career education cannot be a panacea that prepares adolescents for future careers, but it plays a significant role in the effective design of their school life [32]. Career education could promote "the development of knowledge, skills, and attitudes through planned programs of learning experiences in education to assist informed work and study decision-making" [20], p. 55. Patton [21] suggested that career education should include the following three major elements: self-awareness, opportunity awareness, and decision and transition learning.…”
Section: Sports Career Educationmentioning
confidence: 99%
See 1 more Smart Citation